A phase II trial of second‐line axitinib following prior antiangiogenic therapy in advanced hepatocellular carcinoma. Issue 10 (6th January 2015) - McNamara, Mairéad G.; Le, Lisa W.; Horgan, Anne M.; Aspinall, Alex; Burak, Kelly W.; Dhani, Neesha; Chen, Eric; Sinaei, Mehrdad; Lo, Glen; Kim, Tae Kyoung; Rogalla, Patrik; Bathe, Oliver F.; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND Second‐line treatment options in advanced hepatocellular carcinoma (HCC) are limited. Axitinib, a selective potent tyrosine kinase inhibitor (TKI) of vascular endothelial growth factor VEGF) receptors 1, 2, and 3, merits exploration in HCC. METHODS This was a single‐arm phase II trial of axitinib in advanced HCC. Eligible patients were Child‐Pugh A/B7, with measurable progressive disease after TKIs/antiangiogenic drugs. Axitinib was started at 5 mg twice daily orally, titrated from 2 to 10 mg twice daily as tolerated. The primary end point was tumor control at 16 weeks by RECIST1.1; secondary end points were response rate, comparing response by RECIST1.1 to Choi and modified RECIST, exploring dynamic contrast‐enhanced imaging models, safety, progression‐free (PFS), and overall survival (OS). RESULTS Thirty patients were treated. Of 26 patients evaluable for response, there were 3 partial responses (PR) per RECIST1.1; 13 PR by Choi, 6 PR and 1 complete response by modified RECIST. Tumor control rate at 16 weeks was 42.3%. Two‐week perfusion changes were noted on functional imaging. Of 21 patients with evaluable α‐fetoprotein response, 43% had >50% decrease from baseline. Most common axitinib‐related grade 3/4 adverse events (AEs) were hypertension, thrombocytopenia and diarrhea. Of 11 patients with any grade hypertension, 7 had disease control >36wks. Four patients discontinued treatment due to AEs. Median PFS was 3.6months. Median OS was 7.1months. CONCLUSIONS With 42.3% tumor control at 16weeks, primary endpoint was met. Axitinib has shown encouraging tolerable clinical activity in VEGF‐pretreated HCC patients but further study should be in a selected population incorporating potential biomarkers of response. Cancer 2015;121:1620–1627. © 2015 American Cancer Society.